Analysis of genetic structure of the Ukrainian carps of scaled and framed breeds - Глушко, Ю. М.; Тарасюк, С. І. (Problems of Environmental Biotechnology, 2012)
The analysis of genetic structure of carps Ukrainian framed and scaled breeds has been carried out. With help of six genetic-biochemical systems was find out breed specificity of carps genetic structure. Excess of heterozygotic genotypes by loci ALB, MDH, ME, CA was established.